Direct foaming and seeding of highly porous, lightweight gypsum. Issue 15 (15th July 2016) - Roch Isern, Elisabet; Messing, Gary L.
Abstract: Abstract : This paper describes the direct-foaming of plaster of Paris (CaSO4 ·½H2 O) with up to 1.7 wt% of a nonionic surface-active agent to obtain highly porous, lightweight gypsum (CaSO4 ·2H2 O) with 65–70% total porosity and a homogeneous, bimodal pore size distribution. Based on viscosity and temperature changes in the setting plaster of Paris slurry, the nonionic surfactant is seen to retard gypsum crystallization and thus extend the working time at higher water to solid ratios. The increase in viscosity during gypsum crystallization stabilizes the macropores formed during foaming. Gypsum foams of 32% density with a submicron matrix pore size, and relatively uniform macropore size of ∼100 µm were obtained. Seeding the process with 0.5 wt% 100 µm diameter gypsum particles accelerates gypsum crystallization in the presence of the nonionic surfactant and results in a more uniform, finer (92 µm) macropore structure due to less time for bubble coalescence.